Branding through trade shows in the automotive industry - Narui, Jahan (Universitetet i Nordland, 2013)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2013 The automotive industry is a major global industry with a great history of exhibitions. As trade shows are getting more attention within studies, the same is not the case for automotive trade shows. Noteworthy, automotive trade shows emphasize non-selling roles such as image-building. This paper seeks to investigate image-building purposes of exhibiting automotive companies using integrated marketing communications (IMC). Data has been gathered from four participating companies in the Geneva Motor Show. The empirical findings show several reasons to implement IMC in trade show activities to enhance the brand image. By carefully blending the promotional tools the brand image may be enhanced. The findings imply the need for better knowledge within IMC for some companies. The findings also suggest that this relative new marketing concept yields plural benefits. The paper clarifies the image-building purposes of exhibiting automotive companies and leads to proposals for further research in an unexplored area.